GROWTH PROFILES AND ETHANOL PRODUCTION OF TWO YEAST STRAINS Kluyveromyces marxianus IFO-288 AND Kluyveromyces marxianus IFO-617 DURING FERMENTATION OF SOYBEAN PULP HYDROLYZATE SUBSTRATES - Kahar Muzakhar (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2013)
Two yeast strains, K.marxianus IFO-288 and K.marxianus IFO-617, were observed to utilize carbon andnitrogen sources obtained from enzymatically hydrolyzed soybean pulp (hydrolyzate). Under aerobiccondition where 1.5% hydrolyzate was used, the maximum biomass of the two yeast yield reached 30%with the protein contents of 47-53%. The two yeast strains also fermented the soybean pulp hydrolyzateand produced alcohol when anaerobic condition was set. The alcohol production effi ciencies of the K.marxianus IFO-288 and K. marxianus IFO-617were 49% and 59.7%, respectively in the medium containing1.5% hydrolyzate. These values were noticed to decrease for the two strains when the concentration of thehydrolyzate was increased. At the concentrations of 2.5% and 5% hydrolyzate for examples, the alcoholproduction effi ciencies of the K.marxianus IFO-288 became 42.5% and 18.5%, respectively, while 45.6% and20.8%, respectively were recorded in the medium inoculated with K. marxianus IFO-617. At 10% hydrolyzateconcentration, none of the yeast strains grew or produced alcohol, indicating that some inhibitory substancesin hydrolyzates were present in the fermentation medium.